The development of radial line slot array antenna for direct broadcast satellite reception - Lim, T. S.; Tan, K. G. (Taylor & Francis Group, 2007)
Microwave antennas are extensively used in communications systems such as satellite, television and high-speed data transmission due to their wide and absolute bandwidth. Among the variety of microwave antennas, satellite communication commonly adopts an antenna of parabolic dish type, despite some drawbacks. In a primary fed design, there is considerable aperture blockage. An offset parabolic antenna design, which then eliminates the blockage, is susceptible to physical damage as its feed is significantly exposed from the body of reflector. The radial line slot array (RLSA) type antenna is thus designed to cope with the problems encountered in parabolic antennas. RLSA is a planar antenna suitable for direct broadcast satellite (DBS) reception, with advantages including high radiation efficiency (high gain), low profile, low cost and feed rear-mounted. The prototype development started with the selection of the cavity's dielectric material and construction of the feeding structure of coaxial-to-waveguide transition. Within the frequency band of interest, between 10.95 and 11.7 GHz, results, is showed a lower than -10 dB of return loss. A DBS receiver test-bed had been developed to test the constructed antenna prototypes and it revealed that the prototype has the capability of receiving TV programs from DBS.